Hubungan Antara Emotional Focused Coping Dan Dukungan Sosial Terhadap Stres Akademik Pada Mahasiswa Magister Psikologi Di Yogyakarta - Muhammad Dinullah Akbar; Elli Nur Hayati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This research aims to determine the relationship between emotional focused coping and social support on academic stress on psychology students in the Master program in Yogyakarta. This research method is a quantitative method with a Likert scale model as a data collection tool. The subjects of this research were psychology students in the Master program in Yogyakarta, namely three private universities and two state universities. The sampling technique was carried out using a purposive sampling technique. Analysis of research data was carried out using correlation analysis techniques with the help of the SPSS 24 program. The results of the research showed that there was a very significant relationship between emotional focused coping and social support on academic stress for Master of Science/Profession Psychology students in Yogyakarta, with a value of p=0.000 (p< 0.01). The emotional focused coping variable produces a very significant relationship to academic stress with a value of p=0.000 (p<0.01). The social support variable produces a very significant relationship to academic stress with a value of p = 0.000 (p <0.01). Emotional focused coping and social support can be implemented to reduce academic stress for Master of Psychology students in Yogyakarta. The conclusion of this research is that the higher the emotional focused coping and social support received, the more likely it is that students will have low academic stress.